THE ESTIMATION OF COMPENSATORY MYOCARDIAL HYPERTROPHY AND FUNCTIONAL CARDIAC STATE UNDER A DOSED PHYSICAL LOAD - Kovalenko, V.M. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
On the basis of the data of clinical examination and echocardiography was studied the functional significance of compensatory myocardial hypertrophy under conditions of physical load test of sportsmen with myocardial hypertrophy of the left ventricle or without it and patients with different stages of arterial hypertension. The usage of compensatory myocardial hypertrophy indices for diagnostics of the heart failure was grounded.